2010
DOI: 10.1121/1.3506349
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis of the effects of sustained wakefulness on speech

Abstract: Exposing healthy adults to extended periods of wakefulness is known to induce changes in psychomotor functioning [Maruff et al. (2005). J. Sleep Res. 14, 21-27]. The effect of fatigue on speech is less well understood. To date, no studies have examined the pitch and timing of neurologically healthy individuals over 24 h of sustained wakefulness. Therefore, speech samples were systematically acquired (e.g., every 4 h) from 18 healthy adults over 24 h. Stimuli included automated and extemporaneous speech tasks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…The reading samples were used to examine syllable segregation by studying the features of hesitations and within and between word silences using three measures [39], [40]:…”
Section: Methodsmentioning
confidence: 99%
“…The reading samples were used to examine syllable segregation by studying the features of hesitations and within and between word silences using three measures [39], [40]:…”
Section: Methodsmentioning
confidence: 99%
“…For example in [7] it was demonstrated that when subjects were kept awake for a period of 24 hours, the duration of their pauses gradually increased for read speech, and the variation in the 4th formant decreased for sustained vowel sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions for speech recognition systems were explored in that study, and later studies also considered stress classification systems (Cairns and Hansen, 1994;Womack and Hansen, 1996;Bou-Ghazale and Hansen, 2000). Contemporary study of acoustic variability of speech focuses on one type of speech variability at a time, and groups emotions into one category, and situational speaker stressors into another, including cognitive task stress (Lindstrom et al, 2008), Lombard effect (Boril and Hansen, 2010), fatigue (Vogel et al, 2010), and physical task stress. Godin and Hansen (2008) showed that fundamental frequency, and the percent of frames voiced in an utterance, are affected by physical task stress, but that the standard deviation of fundamental frequency in an utterance is not affected.…”
Section: Introductionmentioning
confidence: 98%